Analisis Penerapan Materialitas dan Risiko Audit terhadap Opini Audit di Masa Pandemi oleh KAP KKSP dan Rekan Jakarta - Desi Susilawati; Lusy Estiana (Universitas Pendidikan Indonesia, 2023)
This study aims to find out how KAP KKSP and Partners Jakarta in implementing materiality and audit risk on the audit of PT. XXX. Sources of data in the form of secondary data, namely financial reports, Working Paper, and ATLAS data of PT. XXX 2021. Data analysis using mix methods. Qualitative methods were obtained from descriptive data and quantitative methods to calculate overall materiality, performance materiality, uncorrected threshold values, and audit risk formulas. The results show that the auditors set a materiality level of 1% from assets of 365,087,319,797 so that overall materiality is 3,650,873,198, a margin of 50% of overall materiality so that performance materiality is 1,825,436,599, and a margin of 25% of performance materiality so that the threshold value is not corrected by 456,359,150. The obtained AR 5%, RoMM 70%, and DR 7%, meaning that substantive testing is needed in a way that there is a probability of failure of about 7% in detecting material misstatements. KAP expresses an unqualified opinion based on the analysis and consideration of audit opinions, as well as taking alternative approaches during a pandemic, including additional risk evaluation, virtual physical examination, estimating uncertainty, and utilizing technology.